Peer Counseling as A Coping Strategy for Academic Stress and Burnout in Final-Year Students - Kushendar, Kushendar; Maba, Aprezo Pardodi (COUNS-EDU: The International Journal of Counseling and Education, 2022)
Academic stress is the pressure on students caused by competition and academic demands. This study examines and analyzes peer guidance and counseling (Peer Counseling) to reduce academic stress and academic burnout experienced by final-year students. The research method used was experimental research involving an experimental group and a control group (Pretest-Posttest Control Group Design), with each group member consisting of 20 participants, selecting participants based on a purposive sampling technique. Each participant was assigned a random assignment. The MANOVA test results showed that peer counseling reduced academic stress (F (2.24) = 101.769; ?p2 = 0.85; p <0.01) and burnout (F (2.24) = 21.769; ?p2 = 0.55; p <0.01). Furthermore, the Wilcoxon test results showed that in the experimental group, there was an enhancement in academic stress (Z = -2.82; p <0.05) and burnout (Z = -2.82: p <0.05). The control group showed an enhancement in burnout (Z = -2.17; p < 0.05), but academic stress showed there was no enhancement (Z = -0.34: p > 0.05). Peer counseling (peer counseling) based (on stress management) as a strategy to overcome academic stress and burnout in final-year students in Metro City.